2023
DOI: 10.1097/01.ogx.0000912572.55034.1b
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Vaccination During Early Pregnancy With Risk of Congenital Fetal Anomalies

Abstract: COVID-19 infection increases the risk of maternal and neonatal morbidity in the pregnant population. While data suggest that COVID-19 vaccines are safe and effective during pregnancy, the risk to the fetus is unclear. The aim of this study was to assess the association between COVID-19 vaccination during early pregnancy and the risk of fetal structural anomalies.This was a retrospective cohort study conducted at a single medical center in Chicago. Included were pregnant people with COVID-19 vaccination records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several authors have explored this possibility found no composite increase in anomalies in infants born to mothers who received the vaccine during the first trimester versus those who did not [25,26,27]. Additional reports about vaccine safety during the teratogenic window of gestation only considered congenital anomalies detected via ultrasonography rather than neonatal outcomes [28] allowing the possibility that more subtle anomalies not identified on ultrasound could have been missed. In our cohort during the period considered to be the COVID-19 pandemic (from September 2020 to April 2022), significantly fewer infants were born with congenital anomalies to non-COVID-19 infected mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have explored this possibility found no composite increase in anomalies in infants born to mothers who received the vaccine during the first trimester versus those who did not [25,26,27]. Additional reports about vaccine safety during the teratogenic window of gestation only considered congenital anomalies detected via ultrasonography rather than neonatal outcomes [28] allowing the possibility that more subtle anomalies not identified on ultrasound could have been missed. In our cohort during the period considered to be the COVID-19 pandemic (from September 2020 to April 2022), significantly fewer infants were born with congenital anomalies to non-COVID-19 infected mothers.…”
Section: Discussionmentioning
confidence: 99%
“…An mRNA COVID-19 vaccine did not increase the risk of miscarriage in pregnant women who received the vaccine just before or during early pregnancy (<20 weeks) [83][84][85]87]. Administration of the mRNA COVID-19 vaccine during pregnancy was not associated with an increased risk of complications, including preterm birth, stillbirth, bacterial infection of the placenta, and excessive maternal blood loss after birth [85,87,88]. Furthermore, administration of COVID-19 vaccine before and during the first trimester was not associated with an increased risk of detectable birth defects [88].…”
Section: Vaccinementioning
confidence: 96%